Ovarian Cyst Torsion: A Case Report - Lampus, Harsali; Rendy, Leo; Candy, Candy; Rangan, Andy (Universitas Sam Ratulangi, 2025)
Abstract: Accidents involving ovarian cysts might include cyst rupture, hemorrhage, and torsion. Any girl who has abdominal pain or a pelvic or abdominal mass should be evaluated for ovarian torsion, a rare issue in the juvenile age group. We reported a 10-year-old girl presented with complaints of lower left abdominal pain that began three days prior to her hospital admission. Initially, the pain was intermittent but subsequently became persistent and intensified, with no pain-free intervals. CT-Scan of the abdomen – pelvis without contrast revealed cystic mass with fat components and intralesional calcification, in the suprapubic quadrant. The impression came from the ovary (difficult to determine the right/left ovary), which urged the bladder to the anteroinferior and urged the uterus to the posterior, suspected of mature cystic ovarian teratoma. The patient was managed with intravenous fluids (IVFD), antibiotics, and analgesics for pain control. Due to the high suspicion of ovarian torsion, emergency exploratory laparotomy was performed. Anatomical differences in the paediatric population and their effects on surgery were also be considered. Intraoperative findings confirming a left ovarian cyst measuring approximately 8 x 6 x 4 cm, which had undergone torsion twice. Detorsion was performed, and the ovary was found to be viable. Cystectomy was carried out, preserving healthy ovarian tissue. The right ovary appeared normal. In conclusion, this case underscores the importance of timely surgical intervention, even beyond the traditional